2004
DOI: 10.1007/s00011-004-1258-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and histopathological characterization of Bothrops lanceolatus (Fer de lance) venom-induced edema

Abstract: B. lanceolatus venom produced dose- and time-dependent edema in rat paws. This edema was not dependent on low molecular weight substances in the venom, but was partially dependent on a hemorrhagin and also involved the release of arachidonic acid metabolites, bradykinin, histamine and serotonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 50 publications
0
18
0
2
Order By: Relevance
“…The characteristic thrombotic effect described in human envenoming is not reproduced in the mouse model. Oedema is partially dependent on a “hemorrhagin” and involve the release of arachidonic acid metabolites (by either cyclooxygenase or lipooxygenase), bradykinin, histamine, and serotonin [13]. Both polyvalent Crotalinae and monospecific B. lanceolatus antivenom were shown to immunodeplete B. lanceolatus venoms in vitro and to be fully effective in mice in neutralizing the lethal, hemorrhagic, oedema-forming, myotoxic, and indirect hemolytic activities of the venom [7,14,15].…”
Section: Envonimation Pathophysiologymentioning
confidence: 99%
“…The characteristic thrombotic effect described in human envenoming is not reproduced in the mouse model. Oedema is partially dependent on a “hemorrhagin” and involve the release of arachidonic acid metabolites (by either cyclooxygenase or lipooxygenase), bradykinin, histamine, and serotonin [13]. Both polyvalent Crotalinae and monospecific B. lanceolatus antivenom were shown to immunodeplete B. lanceolatus venoms in vitro and to be fully effective in mice in neutralizing the lethal, hemorrhagic, oedema-forming, myotoxic, and indirect hemolytic activities of the venom [7,14,15].…”
Section: Envonimation Pathophysiologymentioning
confidence: 99%
“…Dexamethasone is widely effective in experimental models of paw edema induced by snake venoms as B. asper [14], B. jararaca [55], B. moojeni [32], B. insularis [1] and B. lanceolatus [34]. In the present study, the edema and hyperalgesia induced by Batroxase were significantly reduced by this steroidal anti-inflammatory drug.…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, pretreatment of animals with HOE-140 (selective B 2 receptor antagonist) or DALBK (selective B 1 receptor antagonist) did not reduce the paw edema induced by Batroxase, which indicates that bradykinin is not involved in this response. Guimarães et al [34] and De Faria et al [21] showed the involvement of bradykinin in paw edema induced by B. lanceolatus venom, however, this mediator did not show to be related to the paw edema induced by the venoms of B. asper [12] and B. jararaca [76].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations